MEKANISME KOMUNIKASI ORGANISASI - Jamil Bazarah (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2020)
The aforementioned communication mechanism is in addition to all relatedelements, planning, fostering and controlling the implementation of generaladministrative and financial operations, conducting and fostering thecooperation of the elements and making reports on the results of theimplementation of activities.While the type of research used is descriptive, that is research that isexploratory, systematically describing or describing the mechanisms oforganizational communication that actually occur from research objects inthe field. For data collection techniques used by interview. from the datacollected, the authors analyze it by means of analysis and qualitativetechniques.In connection with the description above, this research was carried out withthe aim to find out how the coordination service as a manifestation of theimplementation of organizational communication mechanisms.In the implementation of communication there are factors that influence thesuccess of communication that will be carried out, namely human resourcesthat drive, direct and do communication; plans that will facilitate theimplementation of communication mechanisms; as well as procedures whichare a series of work procedures to guarantee cooperation between unitswithin related organizations and agencies.